Epilithon isotope composition as an environmental archive in rivers receiving wastewater: the case of the Grand River, Ontario, Canada - Cejudo, Eduardo; Schiff, Sherry; Aravena, Ramon (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2014)
Epilithon is a complex community of autotrophic and heterotrophic organisms that includes inert, organic and inorganic material and is attached to the surface of submersed rocks. Water samples collected in the Grand River (southwestern Ontario) in April 2011 showed that ammonium concentrations decreased downstream, whereas nitrate varied, largely dependent on weather conditions (concentrations of both chemical species were higher during winter). Epilithon δ15N-TN downstream from the Kitchener wastewater treatment plant oscillated between 0.4 to 23.2‰, and δ13C-TC around -27‰. The wastewater treatment plant effluent consisted of δ15N-NO3- between 12 and 16‰, with a decreasing trend as it traveled downstream; δ15N-NH4+ became enriched downstream (as high as 31‰). Average values for δ13C-DIC were -10.1‰ and δ13C-DOC -26.8‰. It is proposed that the nitrogen and carbon isotope composition of epilithon could be used as a short- or medium-term environmental archive, as it reflects in-stream processes, such as ammonia oxidation, in a river impacted by treated wastewater. The interpretation provided here was limited due to the ample range of events and potential sources, specifically when the nitrogen isotopic composition of nitrate and ammonium was similar. Epilithon is easily collected, processed and analysed and proved to be valuable tool to describe changes in river and stream geochemistry.